1991
DOI: 10.1111/j.1365-2958.1991.tb02102.x
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the haemolysin transport process through the secretion from Escherichia coli of PCM, CAT or β‐galactosidase fused to the Hly C‐terminal signal domain

Abstract: Secretion of haemolysin (HlyA) is secA independent, but depends upon two accessory membrane proteins, HlyB and HlyD, encoded by the hly determinant. A fourth (cytoplasmic) protein, HlyC, is required to activate HlyA post-translationally, but has no role in export. Deletion studies have previously shown that the HlyA molecule contains a targeting signal close to the C-terminus which specifically directs its secretion to the medium. This targeting signal has been variously located within the terminal 27, 53, 60 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
52
0

Year Published

1992
1992
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 72 publications
(55 citation statements)
references
References 45 publications
3
52
0
Order By: Relevance
“…Not surprisingly, PddA, -B, -C, and -D are homologs of PulG, -H, -I, and -J. Amino-terminal cleavage of the leader sequence from the precursor of PulG by PulO has also been confirmed (47). Other homologs of type IV pilins involved in extracellular secretion of enzymes from E. chrysanthemi and X. campestris have also recently been described (7,15 mammalian prochymosin (25). In each case, only a fraction of hybrid protein synthesized was released from E. coli; however, the observed extracellular secretion was always dependent on the presence of the HlyB-HlyD translocator proteins.…”
Section: Extracellular Secretion Of Proteinsmentioning
confidence: 88%
“…Not surprisingly, PddA, -B, -C, and -D are homologs of PulG, -H, -I, and -J. Amino-terminal cleavage of the leader sequence from the precursor of PulG by PulO has also been confirmed (47). Other homologs of type IV pilins involved in extracellular secretion of enzymes from E. chrysanthemi and X. campestris have also recently been described (7,15 mammalian prochymosin (25). In each case, only a fraction of hybrid protein synthesized was released from E. coli; however, the observed extracellular secretion was always dependent on the presence of the HlyB-HlyD translocator proteins.…”
Section: Extracellular Secretion Of Proteinsmentioning
confidence: 88%
“…Figure 2A shows that aggregated protein could be recovered from the culture fluids of cells synthesizing RsaA242C, RsaA166C, RsaA134C, and RsaA119C, indicating that all of these C-terminal peptides of RsaA were capable of autonomous secretion. The autonomous secretion of the 119-aa C-terminal peptide indicated that an RTX motif was not absolutely required for secretion, a conclusion reached for other proteins secreted by type I systems (10,12,16,18).…”
mentioning
confidence: 96%
“…Although the presence or absence of the RTX sequences is unlikely to be responsible for the aggregation of hybrid proteins, these sequences are likely to affect the kinetics and efficiency of the secretion process (11). It has also been shown that the importance of including RTX motifs in a hybrid protein varies with the particular passenger protein (10,18,19).…”
mentioning
confidence: 99%
See 2 more Smart Citations